Comparison of hemodynamic response to tracheal intubation with Macintosh and McCoy laryngoscopes - Mehtab A Haidry; Fauzia A Khan (Wolters Kluwer Medknow Publications, 2013)
Background: Use of McCoy blade laryngoscope avoids the lifting force in the vallecula and theoretically should lead to a lower hemodynamic response related to laryngoscopy and tracheal intubation. The available literature on the topic is conflicting. Materials and Methods: We studied the hemodynamic response to laryngoscopy and tracheal intubation in 60 ASA 1 AND 2 adult patients using either Macintosh or McCoy laryngoscopes. The change in systolic, diastolic, mean arterial pressure, and heart rate (HR) was observed for 10 min post intubation. Arrhythmias and ST changes were also observed. Results: The maximum change in HR was 18.7% in the Macintosh and 7.7% in the McCoy group, and in systolic arterial pressure was 22.9% in the Macintosh and 10.3% in the McCoy group. This difference between groups was significant ( P < 0.0001). The change lasted for a lesser duration in the McCoy group. No arrhythmias or ST changes were observed in either group. Conclusion: Hemodynamic changes with use of McCoy laryngoscope were lesser in magnitude and of shorter duration.